(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background : Badminton requires a specific physical conditioning in terms of motor and action controls; coordinative variables such as reaction time, foot stepping and static or dynamic balances, which are essential motor demands in this sport. Therefore, badminton players need enough core strength and a high level of dynamic balance during the rapid postural movements around the court. Objectives : To study the effect of core strengthening and to study the effect of conditioning program on badminton beginners Methodology : 25 players, aged between 12-19 years were given core strengthening and conditioning protocol for 4 weeks. Players were assessed at 0, 2nd and 4th week through 60 degree curl up test and modified Sorensen test. Results : statistically significant difference was seen in pre and post treatment values of the 2 tests. In 60 degree curl up test at 0 week p=, 2nd week p= and 4th week p= and in modified Sorensen test at 0 week p=, 2nd week p= and 4th week p= Conclusion : players showed improvement in their core strength after 4 weeks of core training.